2020
DOI: 10.3390/pharmaceutics12080723
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Polymeric Nanoparticles Based on Ketoprofen and Dexamethasone

Abstract: Polymeric nanoparticles that combine dexamethasone and naproxen reduce inflammation and synergistically inhibit Interleukin-12b (Il12b) transcription in macrophages. This effect can be the result of a cyclooxygenase-dependent or a cyclooxygenase-independent mechanism. The aim of this work is to obtain potent anti-inflammatory polymeric nanoparticles by the combination of dexamethasone and ketoprofen, one of the most efficient cyclooxygenase-inhibitors among non-steroidal anti-inflammatory drugs, with appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 41 publications
3
23
1
Order By: Relevance
“…The Dex-S/P(5:1)-NS showed a gradual decrease in macrophage infiltration, but AgS-S/P(5:1)-NS suppressed macrophage infiltration at 2 weeks and then slightly increased at 3 weeks. This result indicates that sustained drug release is required to suppress macrophage infiltration because Dex and AgS display potent inflammatory suppressive properties [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Dex-S/P(5:1)-NS showed a gradual decrease in macrophage infiltration, but AgS-S/P(5:1)-NS suppressed macrophage infiltration at 2 weeks and then slightly increased at 3 weeks. This result indicates that sustained drug release is required to suppress macrophage infiltration because Dex and AgS display potent inflammatory suppressive properties [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among these factors, NO overproduction plays a major regulatory role in tissue damage associated with chronic inflammation presented in OA. Different polymeric NPs have demonstrated a reduction of NO in LPS-stimulated RAW264.7 encapsulating CLX [ 28 ] and DEX [ 23 , 63 , 64 ]. Unloaded NPs were deeply studied in a previous work and the reduction in NO production was not observed in LPS-stimulated RAW264.7 macrophages [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, considerable work trying to combine DEX with nanotechnology has been developed, since DEX possesses powerful anti-inflammatory activity, even at low doses [ 19 ]. It has been recently encapsulated alone [ 20 , 21 , 22 ], or in combination with other factors, such as other anti-inflammatory molecules like ketoprofen [ 23 ] or small interfering RNA [ 24 ], and covalently conjugated, for example, with the avidin protein [ 25 ] with positive effects both in vitro and in vivo. In the case of CLX, CLX poly(1-vinyl-2-pyrrolidone) solid dispersion NPs [ 26 ], or CLX-loaded hyaluronan NPs [ 27 ], were prepared to improve this drug bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes MTX, Dex, SIN Improved controlled release, reduced RA signs, decreased side effects [128] Polymeric NPs Ket, Dex, TFC, MTX Decreased inflammation [134] Niosomes PC, thiocolchicoside, ibuprofen Increased drug retention [143] Silver NPs FA-AgNPs Enhanced anti-inflammatory activities [148] Gold NPs Triam Enhanced anti-inflammatory activities [150] Iron NPs MTX Suppression of joint edema and inflammation [152] Quantum dots celecoxib Localized activity in sites of inflammation [153] Solid lipid NPs CUR, Pi, CIP Enhanced anti-inflammatory activities [154] Polymeric micelles Dex, indomethacin Decreased side effects [159] Abbreviations: NPs, nanoparticles; MTX, methotrexate; Dex, dexamethasone; SIN, sinomenine hydrochloride; Ket, Ketoprofen; TFC, tofacitinib; PC, piroxicam; FA-AgNPs, folic acid modified with silver nanoparticles; Triam, triamcinolone; CUR, curcumin; Pi, piperine; CIP, ciprofloxacin; RA, rheumatoid arthritis; COX-2, cyclooxygenase 2.…”
Section: Drugs Effects Referencesmentioning
confidence: 99%
“…Espinosa-Cano et al [ 134 ] demonstrated the benefits of using polymeric NPs conjugated with naproxen and Dex to decrease inflammation and prevent IL-12 expression in macrophages. Note that IL-12 and IL-23 recently appeared as therapeutic targets in the therapy of long-lasting inflammatory disorders in which T cells are the primary dysfunctional immune cells, via either COX-dependent or COX-independent regulation mechanisms.…”
Section: Nanomaterials For the Treatment Of Inflammatory Arthritismentioning
confidence: 99%